Sistem Informasi Rekam Medis Berbasis Web Pada Klinik Risa Rafana Menggunakan Metodologi Extreme Programming - Jihadul Akbar; Ainul Yaqin (Fakultas Teknik Universitas Hamzanwadi, 2021)
Risa Rafana is a clinic that located at Wage Batujai West Praya, Central Lombok, West Nusa Tenggara Province. Risa Rafana clinic has problems in medical records processing because the existing system could not systematically assess patient, so the clinicians had trouble for finding the data of patients when had been in manual system. The is development method that was used is Extreme Programming methodology. The method prioritizing of clients as a resource person who understand the system that will be created, from the client itself acquired user story. The Stages that will be created such as planning, design, coding and testing. The information system is designed by concept of UML (Unified Modeling Language) and developed using Framework PHP (Hypertext Preprocessor), which is a web-based CodeIgniter. The processing of database by MySQL. The information system could process data of patients, doctors, specialists, labs, rontgen, medications, so it could make medical records information and made report of patient’s surgery, reporting of laboratory check, reporting of medicine prescription, reporting of drug selling that has been given to patients, so it made easier to diagnose the disease